MEDIUM AND LOW FREQUENCY ELECTROTHERAPY IN THE MUSCLE STRENGTH (Fiep Bulletin - online, 2020)
Introduction: Neuromuscular electrical stimulation (NMES) has been used as one of the pillars of the therapeutic modalities for the gain of muscle strength. Objective: To compare the strength gain in the elbow flexor muscles in women after the use of Neuromuscular Electrical Stimulation (NMES) of low and medium frequency.  Materials and Methods: 15 women were selected, with normal body mass index (BMI), previously healthy, sedentary and aging from 18 to 27 years old. They were randomically separated in 2 groups, Russian current (n=8) and low frequency (FES) group (n=7), with the stimulation only in the weakest arm of the participants. FES frequency was 50Hz, pulse duration of 200 microseconds and Russian current, medium frequency alternating current of 2,500 Hz, was modulated to 50Hz, duty cycle of 50%, for both methods the ramp-up and ramp-down was 2 seconds, 20 seconds of ON and OFF time, for 20 minutes in the triceps brachii, for 5 weeks, with intensity enough to promote a muscle contraction visible and tolerable. Strength measurements were made with a portable dynamometer before the start of the NMES protocol and after the end of it. Results: we used the paired T test and the T Student test with the significance level set to p